Cigarette Smoke Extract-Induced Oxidative Stress and Fibrosis-Related Genes Expression in Orbital Fibroblasts from Patients with Graves' Ophthalmopathy - Kau, Hui-Chuan (Oxid Med Cell Longev, 2016)
Cigarette smoking is the most important risk factor for the development or deterioration of Graves' ophthalmopathy. Smoke-induced increased generation of reactive oxygen species may be involved. However, it remains to be clarified how orbital fibroblasts are affected by cigarette smoking. Our study demonstrated that Graves' orbital fibroblasts have exaggerated response to cigarette smoke extract challenge along with increased oxidative stress, fibrosis-related genes expression, especially connective tissue growth factor, and intracellular levels of transforming growth factor-β1 and interleukin-1β. The findings obtained in this study provide some clues for the impact of cigarette smoking on Graves' ophthalmopathy and offer a theoretical basis for the potential and rational use of antioxidants in treating Graves' ophthalmopathy.